Litter to Leaf: The Unexplored Potential of Silk Byproducts. Issue 7 (July 2021) - Reddy, Roopa; Jiang, Qiuran; Aramwit, Pornanong; Reddy, Narendra
Abstract : Silk has remained the most preferred protein fiber since its discovery in 3000 BC. However, the cost, availability, and resources required to rear the silkworms and process silk are imposing considerable constraints on the future of silk. It is often unrealized that apart from the fibers, production and processing of silk are a source for a diverse range of sustainable, biodegradable, and biocompatible polymers. Hence, delineating itself from being the primary source of protein fibers for millenniums, the silk industry worldwide is transitioning into a biobased industry and as a source for pharmaceuticals, biomaterials, cosmetics, food, and energy. Toward this, byproducts (BPs) and co-products (CPs) that are inevitably generated are now being considered to be of immense economic value and could be up to 10 times more valuable than the silk fibers. Here, we elucidate the properties and potential applications of silk BPs and CPs to present the true potential of silkworms and to promote the establishment of silkworm-based bioeconomy and biorefineries. Highlights: Silkworms are biofactories that generate proteins, lipids, and polysaccharides. Sericin, pupae, litter, and mulberry leaves contain valuable biomolecules. The values of these biomolecules could be three to five times the value of silk fibers. Proteins in pupae and litter show anticancer and antiviral activities. In the future, silkworms could be reared for their immensely valuable byproducts rather than their fiber-producing cocoons.